Kajian Manajerial Efektifitas Pemeliharaan Jaringan dan Transformator Distribusi 20 kV Menggunakan Uji ANOVA - Hari Kaptono Adi (Jurnal Sinergi Jurusan Teknik Mesin, 2023)
PT PLN (Persero) is an electricity company in Indonesia which supports the development and industrial sectors. Process Business PLN starts from power plant, Transmission and distribution until Retail to Customers. For Supply the needed for customer in electricity power, PLN keep the reliability electricity network for fulfil it. The reliability of electric power distribution network depends on several factors, including the quality of materials, maintenance, operating patterns, protective equipment used and also network configuration. One of the ways to maintain electricity service is to carry out distribution transformer maintenance. After the maintenance is carried out, it is necessary to evaluate the distribution transformer maintenance activities that have been carried out, whether the maintenance activities have an impact or not on management, this is measured by the quality of the voltage and the rupiah per kWh that can be distributed and is denominated in rupiah. The purpose of this study is to find out whether the network and transformer maintenance has had an impact or not. One way that can be done statistically is through the ANOVA test. From the result, Minitab results obtained a value of 0.321 > α = 0.05 and the results of the autocorrelation do not show plots that are outside the lines or margins. This means that the maintenance activities of the 20 kV distribution transformers in data collection unit affect the company’s income. This means that maintenance activities affect the company's income. Therefore, the maintenance factor affects the company's income. Thus, it can be the main focus for improving distribution reliability by doing transformer 20 kV maintenance.